2004
DOI: 10.1590/s0100-879x2004000800001
|View full text |Cite
|
Sign up to set email alerts
|

A high-copy T7 Escherichia coli expression vector for the production of recombinant proteins with a minimal N-terminal His-tagged fusion peptide

Abstract: We report here the construction of a vector derived from pET3-His and pRSET plasmids for the expression and purification of recombinant proteins in Escherichia coli based on T7 phage RNA polymerase. The resulting pAE plasmid combined the advantages of both vectors: small size (pRSET), expression of a short 6XHis tag at N-terminus (pET3-His) and a high copy number of plasmid (pRSET). The small size of the vector (2.8 kb) and the high copy number/cell (200-250 copies) facilitate the subcloning and sequencing pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
133
0
50

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 260 publications
(184 citation statements)
references
References 16 publications
1
133
0
50
Order By: Relevance
“…The acquisition of hostderived PLA by leptospiral receptor-bound PLG can degrade fibronectin and laminin that may aid bacterial propagation (Vieira et al, 2009;. By data mining the available genome sequences of L. interrogans (Nascimento et al, 2004), we have identified novel hypothetical proteins, several of them described as PLGbinding proteins Oliveira et al, 2011;Souza et al, 2012;Vieira et al, 2010b). Lsa44 and Lsa45 proteins are also able to bind PLG that is converted to functional PLA in the presence of uPA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The acquisition of hostderived PLA by leptospiral receptor-bound PLG can degrade fibronectin and laminin that may aid bacterial propagation (Vieira et al, 2009;. By data mining the available genome sequences of L. interrogans (Nascimento et al, 2004), we have identified novel hypothetical proteins, several of them described as PLGbinding proteins Oliveira et al, 2011;Souza et al, 2012;Vieira et al, 2010b). Lsa44 and Lsa45 proteins are also able to bind PLG that is converted to functional PLA in the presence of uPA.…”
Section: Discussionmentioning
confidence: 99%
“…The gene sequence was amplified without the signal peptide tag. The PCR fragments of 1212 bp (LIC10645) and 1164 bp (LIC10731) were ligated into the E. coli expression vector pAE (Ramos et al, 2004) at the restriction sites presented in Table 1. This expression vector allows the inclusion of a His 6 epitope at the N-terminus of the recombinant proteins.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…aRrp42 (PH1548) was amplified using primers aRrp42for (5Ј-AGGGATCCCATATGAGTGATA-ATGAGATCG-3Ј) and aRrp42rev (5Ј-ATCTGCAGATTAGGTA-AATATTACTCC-3Ј); the restriction sites for BamHI, NdeI, and PstI are underlined. NdeI-and PstI-digested DNA of aRrp42 was inserted into the expression vector pAE (15). aRrp4-aRrp41 were amplified using primer aRrp4for (5Ј-CGGATCCCATATGAAGAGGATTTTTGTTC-3Ј) and reverse primer for aRrp41 (aRrp41rev).…”
Section: Methodsmentioning
confidence: 99%